Hubungan Antara Kepemimpinan Transformasional Kepala Sekolah terhadap Peningkatan Motivasi Kerja Guru Era Pendidikan Modern di SMK Tritech Informatika Medan - Abdul Rohim Husaini Wijaya; Abdul Fattah Nasution; Syafri Fadillah Marpaung (Jurnal Budi Pekerti Agama Islam, 2024)
The research that has been conducted is entitled "The Relationship Between Principal Transformational Leadership and Increasing Teacher Work Motivation in the Modern Education Era at SMK Tritech Informatika Medan" which is based on the fact that Principal Transformational Leadership is a leadership model that allows a leader to change the energy of resources, both human, instrument, and situation, to achieve targeted goals. In the context of education, Principal Transformational Leadership is very important to improve the quality of education and increase teacher job satisfaction. The purpose of this study is to determine whether there is a significant relationship between variables X and Y. The methodology of this study uses a quantitative approach with the type of field research. The population of this study were teachers at SMK Tritech Informatika Medan with a sample size of 40 teachers. The sampling technique was carried out by simple random sampling. Data collection techniques by distributing questionnaires, interviews, observations, and documentation. Data management tools by conducting several tests such as validity and reliability tests, normality and homogeneity tests, linearity tests and simple linear regression tests. And for the results of the hypothesis test using the Pearson correlation test method and the paired sample T-Test test. The results of the study revealed that the results of the Pearson correlation test analysis showed that there was a significant influence between the relationship between the principal's transformational leadership and the work motivation of teachers in the modern education era at SMK Tritech Informatika Medan, which was 0.018< 0.05. This shows that variables X and Y are correlated. Then the degree of relationship between variables X and Y of 0.374 shows that the Pearson correlation value of 0.21 to 0.40 between variables X and Y is a weak correlation. And in the second test, namely the paired sample T-Test, the Sig. (2-tailed) value was 0.000 <0.05, so it can be concluded that there is a significant difference between variables X and Y.